Association of heparan sulfate proteoglycan with the neurofibrillary tangles of Alzheimer's disease - Perry, G (J Neurosci, 1991)
The major intracytoplasmic lesion of Alzheimer's disease is the neurofibrillary tangle (NFT), which is primarily composed of paired helical filaments (PHFs). The mechanism responsible for the formation of PHFs, as well as their insolubility and apparent heterogeneity, is unknown. We found that basic fibroblast growth factor (bFGF) binds to heparinase-sensitive sites in NFTs. bFGF binding is due to a heparan sulfate proteoglycan (HSPG) immunocytochemically identified in NFTs. In the presence of polycations (e.g., Ca2+), HSPG will bind to free carboxyl groups in NFT proteins. HSPG binding may play a role in transforming normal soluble proteins into insoluble PHFs.